Effectiveness Profile of Antihypertension Use in Ischamic Stroke Patients in the Inpatient Installation of Muhammadiyah Hospital, Jombang - Puspita Raras Anindita (Program Studi Farmasi, Universitas Ma Chung, 2026)
Background: Cardiovascular disease and cancer are the leading causes of death globally. Stroke is characterized by sudden clinical symptoms lasting more than 24 hours or leading to death due to impaired cerebral circulation. Objective: This study aims to determine the effectiveness of antihypertensive treatment in ischemic stroke patients at the Inpatient Installation of Muhammadiyah Hospital, Jombang. Methods: This research utilized a non-experimental retrospective design with purposive sampling. Evaluated drugs included Angiotensin Receptor Blockers (ARBs), Calcium Channel Blockers (CCBs), Angiotensin-Converting Enzyme Inhibitors (ACEIs), Beta-blockers, and diuretics. Results: The study included 50 patients; 52% were male and 64% were over 60 years old. CCB (Amlodipine) was the most used monotherapy (64.3%), while CCB+ARB (Amlodipine+Candesartan) was the most common combination (62.5%). CCBs showed the highest average blood pressure reduction (14/9 mmHg) and the shortest average length of stay (4.4 days). Conclusion: Both single and combination antihypertensive therapies were effective, with CCBs being the most frequently prescribed and efficient in reducing blood pressure and hospitalization duration.